Pemetaan Riset Sumber Daya Manusia 2010-2015 - Carmelia, Reisy Ratna; , Dr. Edi Purwo Saputro, SE, M.Si (2016)
The objectives of this research were to identify and to conduct a mapping related to the researches of human resources in 2010-2015 by reviewing several empirical researches. The results of the research showed that the researches of human resource were conducted through many kinds of approach models, samples, variables, observation settings, andanalysis tools. The results of the study showed that there was an opportunity to develop a continuation research although there were several weaknesses in this study.